Transformation of amorphous calcium phosphate to monoclinic nano-hydroxylapatite - Yan, Yao (2023)
Monoclinic nano-hydroxylapatite (nHAp) rarely forms at room temperatures, especially from amorphous calcium phosphate (ACP) precursors. We developed a method to synthesise monoclinic nHAp from ACP without crystallisation inhibitors at 25 °C. Additionally, Raman spectroscopy was identified as a reliable technique for observing the crystallisation process.